A New CT Parameter for Predicting Residual Hearing Preservation in Cochlear Implantation: The "Basal Turn–Facial Ridge Angle". Issue 2 (February 2021) - Kim, Hantai; Choo, Oak-Sung; Ha, Jungho; Jang, Jeong Hun; Park, Hun Yi; Choung, Yun-Hoon
Abstract : Objectives: We suggest a simple measurement, called the "basal turn–facial ridge (BT–FR) angle, " for determining the electrode insertion axis using preoperative temporal bone computed tomography (CT) to predict hearing preservation (HP) in cochlear implantation (CI). Study Design: Retrospective chart review. Setting: Tertiary referral center. Patients: Eighty-two ears that underwent CI between 2010 and 2018 were included. Ears with preoperative thresholds less than or equal to 80 dB HL at 125, 250, and 500 Hz were enrolled and grouped using the criteria of Skarżyński et al.: Group 1, complete or partial HP; Group 2, minimal HP or complete hearing loss. Intervention: All subjects underwent CI with soft surgery techniques through the round window approach. Main Outcome Measures: The BT–FR angle is the angle between the basal turn line (BT-line), which is a straight line passing through the center of the longitudinal axis of the BT, and the facial ridge line, which is a straight line running from the endpoint of the BT-line to a point just above the facial ridge. Results: The BT–FR angle was 2.5 ± 2.9 degrees in Group 1 and –0.3 ± 2.7 degrees in Group 2 ( p  = 0.003). The angle and hearing loss showed a significant negative correlation ( r  = –0.401, p  = 0.002). In multiple linear regression, "age at operation" ( β coefficient 0.260; p  = 0.001) and the "BT–FR angle" (–1.967; p  = 0.001) were significant variables affecting the degree of residual hearing loss. Conclusions: The BT–FR angle, which can be measured simply, may be useful to predict residual HP after CI.